Family factors and depressive symptoms among college students: Understanding the role of self-compassion. Issue 7 (2nd October 2020) - Hood, Caitlyn O.; Thomson Ross, Lisa; Wills, Nathan
Abstract: Objective: Poor family support and increased family unpredictability during childhood have been related to subsequent depression. How self-compassion might influence the relation between family factors (ie, unpredictability and support) and depression is unclear. The present study examines how family factors and self-compassion relate to depressive symptoms. Participants: Study participants include 365 university students. Methods: Undergraduate students responded to a questionnaire assessing family factors, recent depressive symptoms, and self-compassion. Results: Hypotheses were supported: family factors were correlated with depression and lower self-compassion, and self-compassion and depression were negatively related. Furthermore, self-compassion moderated the unpredictability-depression relationship. Specifically, individuals who reported high levels of self-compassion demonstrated similar rates of depression, regardless of whether they reported mild, moderate, or high levels of family unpredictability. Self-compassion did not moderate the family support-depression relationship. Conclusions: Implications for therapeutic interventions targeting self-compassion for alleviating depressive symptoms are discussed.